NGHIÊN CỨU SỰ TẠO PHỨC ĐƠN, ĐA PHỐI TỬ CỦA MỘT SỐ NGUYÊN TỐ ĐẤT HIẾM (Ho, Er, Tm, Yb, Lu) VỚI L-METHIONIN VÀ AXETYL AXETON TRONG DUNG DỊCH BẰNG PHƯƠNG PHÁP CHUẨN ĐỘ ĐO pH - Uyển, Nguyễn Trọng; Thiềng, Lê Hữu; Vân, Nguyễn Thuý (Vietnam Journal of Chemistry, 2012)
The stability constant of the mixed ligand complexes and simple ligand complexes formed between Ho3+, Er3+, Tm3+, Yb3+, Lu3+ with L-Methionine and Acetylacetonane (HAcAc) were determined by potentiometric, titration in aqueous solution (30±1oC; I = 0.1). The complexes following 1:2 proportion have form of LnMet2+, LnAcAc2+, Ln(AcAc)2+; following 1:2:2 proportion; 1:4:2 proportion have form of LnAcAcMet+, Ln (AcAc)2Met. The mixed ligand complexes turned out to be much stronger than the simple ligand complexes. Keywords: Some race earth elements, simple and mixed ligand, L-methionine and Acetylacetonane, potentionmetric titration, the simple and mixed ligand complexes.